2022
DOI: 10.3390/agronomy13010094
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture and Nutrient Changes of Agroforestry in Karst Plateau Mountain: A Monitoring Example

Abstract: To explore soil nutrients and moisture changes in different karst mountain agroforestry, in the plateau mountains of Southern China Karst, we used secondary tree and irrigation forest (C) as a reference for our study and selected four mixed agroforestry species (walnut + maize + potato (HYM), walnut + maize (HTY), poplar + ryegrass (YSH), and maize + ryegrass (YMH)) for comparison. First, soil moisture change characteristics were monitored in situ in the field. Second, for soil samples, soil bulk density, poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It also has multiple uses, such as timber production, and provides various products, such as fruit, fodder, food, and industrial raw materials, such as multipurpose woodlots (MWLs). After years, it has been shown that the development of AFS in KD areas not only maximizes its soil and water conservation benefits [12,13,35] but also has a positive effect on improving the productivity of KD areas and maintaining soil faunal diversity [36,37]. It highlights the promising development of AFS in KD areas.…”
Section: Introductionmentioning
confidence: 99%
“…It also has multiple uses, such as timber production, and provides various products, such as fruit, fodder, food, and industrial raw materials, such as multipurpose woodlots (MWLs). After years, it has been shown that the development of AFS in KD areas not only maximizes its soil and water conservation benefits [12,13,35] but also has a positive effect on improving the productivity of KD areas and maintaining soil faunal diversity [36,37]. It highlights the promising development of AFS in KD areas.…”
Section: Introductionmentioning
confidence: 99%